MORAL HAZARD RISK IN THE PRE-VERIFICATION REFUND MECHANISM AND ITS IMPLICATIONS FOR MERCHANTS' LEGAL CERTAINTY - Aisha Salsabila; Rois Harliyanto (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
The development of trade through electronic systems (PMSE) has pushed e-commerce platforms from intermediaries to private regulators that establish transaction mechanisms, including pre-verified refund policies. This could create an imbalance in the distribution of risk between consumers and merchants. This study aims to analyze the suitability of the mechanism to the legal principles set forth in Government Regulation Number 80 of 2019 and its implications for legal certainty and merchants protection. This research is a normative legal research with a legislative and conceptual approach. The analysis is supported by limited empirical interview data that is used to strengthen normative arguments. The results of the study show that the pre-verification refund mechanism creates an unbalanced structure due to the absence of an initial control mechanism (ex ante control), thereby creating space for structural moral hazards. In these conditions, consumers are in a position with minimal risk, while merchants bear the risk of transactions from the outset without adequate verification. The implication is that legal certainty for merchants is only formal, not substantive, because transaction outcomes become unpredictable. In addition, most legal protections still rely on repressive approaches and lack effective preventive mechanisms. This study confirms that moral hazard in e-commerce transactions is not solely due to individual behavior but is a consequence of the platform's policy design. Therefore, it is necessary to reconstruct the refund mechanism by making verification a prerequisite, strengthening preventive measures, and balancing risk allocation to achieve substantive legal certainty in the PMSE ecosystem.